Comparison Between Simulated and Actual Unilateral Hearing in Sequentially Implanted Cochlear Implant Users, a Cohort Study - van Zon, Alice; Smulders, Yvette E.; Kraaijenga, Veronique J. C.; van Zanten, Gijsbert A.; Stokroos, Robert J.; Stegeman, Inge (Frontiers in Surgery, 2019)
Introduction: Previous studies have proven the effectiveness of bilateral cochlear implantation compared to unilateral cochlear implantation. In many of these studies the unilateral hearing situation was simulated by switching off one of the cochlear implants in bilateral cochlear implant users. In the current study we assess the accuracy of this test method. Does simulated unilateral hearing (switching off one cochlear implant) result in the same outcomes as real life unilateral hearing with one cochlear implant and a non-implanted contralateral ear? Study design: We assessed the outcomes of one arm of a multicenter randomized controlled trial. Methods: In the original trial, 38 postlingually deafened adults were randomly allocated to either simultaneous bilateral cochlear implantation or sequential bilateral cochlear implantation. In the current study we used the data of the sequentially implanted group (n = 19). The primary outcome was speech perception-in-noise from straight ahead. Secondary outcomes were speech perception-in-silence, speech intelligibility-in-noise from spatially separated sources and localization capabilities. A within-subjects design was used to compare the results of hearing with one cochlear implant and a non-implanted contralateral ear (1- and 2-year follow-up) with the results of switching off one cochlear implant after sequential bilateral implantation (3-year follow-up). Results: We found no significant differences on any of the objective outcomes after 1-, 2-, or 3-year follow-up. Conclusion: This study shows that simulating unilateral hearing by switching off one cochlear implant seems a reliable method to compare unilateral and bilateral hearing in bilaterally implanted patients. Clinical Trial Registration: Dutch Trial Register NTR1722.